Respon Intelektual Muslim Indonesia terhadap Konsep Islamisasi Ilmu Pengetahuan dalam Konteks Milenial - Sri Wahyuni; M Sholih Salimul Uqba; Istiadah Istiadah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Islamization of science movement is important to study because of Muslim intellectuals' concerns about the scientific crisis faced by Muslims due to the influence of secular Western science. Previous research often only discusses theoretical aspects without linking them to concrete challenges in the millennial era. Therefore, the problem formulation in this study focuses on how Muslim intellectuals respond to the idea of Islamization of science and its relevance in the current social, cultural and technological context. This research used a descriptive-analytical-critical qualitative approach to understand the views of Muslim intellectuals. Data were obtained through document analysis, which were then analyzed using thematic analysis method to identify emerging patterns and themes. The results show that the integration of Islamic values with modern science has significant relevance, especially in providing ethical guidance in dealing with technological developments. A significant new finding is that the Islamization of science can serve as a solution in maintaining cultural and Islamic identity in the midst of rapid globalization. Recommendations for future research include the need for more integrated policy development between Islamic education and modern science, as well as more in-depth analysis of the practical implications of the Islamization of science in the context of Muslim societies.